Studying Myostatin as a Diagnostic Indicator in Sera of Iraqi Women with Metabolic Syndrome (Baghdad Science Journal, 2024)
Obesity in the abdominal area, insulin resistance, hyperglycemia, dyslipidemia, and hypertension are all included as part of metabolic syndrome. Myocytes manufacture and release the myokine known as myostatin, which acts on muscle cells inhibiting cellular growth. This study aimed to compare Myostatin along with other biochemical parameters (Fasting blood sugar (FBS), cholesterol, high-density lipoprotein (HDL), triglycerides (T.G), low-density lipoprotein (LDL), and very Low-density lipoprotein (VLDL)) in sera of Iraqi with metabolic syndrome patients and healthy subjects. Eighty women were separated into two groups: group I, 40 metabolic disorders patients, and group II, 40 healthy people, which served as the control group. Myostatin levels significantly increased compared to the control group in the group with metabolic syndrome, according to the data p > 0.001. A definite cut-off value was visible on the Myostatin ROC curve (5), in the metabolic syndrome. The outcomes suggest myostatin as possible diagnostic tool for metabolic syndrome.